Vincent le Blanc as the second non-muslim in Makkah and Madinah - Spahic, Omer (University of Management and Technology, 2021)
This article discusses the case of Vincent le Blanc as the second European non-Muslim to visit Makkah and Madinah. The article argues that, in reality, the man never did as claimed. The visit was staged mainly for the interests of Christian anti-Islamic polemics. The justification of the contention is two-pronged. Le Blanc’s fallacious, self-contradictory and irrational accounts of Makkah and Madinah, their holy mosques, and of hajj rituals, are firstly presented. That is followed by examining his extensive plagiarism of Ludovico di Varthema.